2017
DOI: 10.1108/ijcst-03-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seam types on seam quality of outdoor clothing

Abstract: Purpose The purpose of this paper is to propose a rational and complete design scheme of seam type of outdoor clothing, so as to improve the seam efficiency and appearance of outdoor clothing, as well as to provide an optimal seam base for the subsequent pressure adhesive process. Design/methodology/approach Four types of common outdoor fabrics and four seam types were selected. Seam strength and thickness were measured. Seam efficiency and seam thickness strain were calculated to evaluate seam quality. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…24 Besides sewing threads, reasonable seam type also needs to be designed for different clothes or different parts of the garment. Shi et al 25 found that seam type has a significant influence on seam strength, and the seam efficiency of outdoor clothing can be increased by the increasing of stitches and the interaction among fabrics.…”
mentioning
confidence: 99%
“…24 Besides sewing threads, reasonable seam type also needs to be designed for different clothes or different parts of the garment. Shi et al 25 found that seam type has a significant influence on seam strength, and the seam efficiency of outdoor clothing can be increased by the increasing of stitches and the interaction among fabrics.…”
mentioning
confidence: 99%
“…[4][5][6] Moreover, the production and R&D (research and development) cost of outdoor clothing was also relatively high because of resisting the external harsh environment. 4,7,8 Additionally, if the stain deposited on surface of clothing did not be removed in time, it was not only easy to occur the protective function of outdoor clothing declining, but also easily breed bacteria and even harm the human body. [9][10][11] In addition, according to the existing studies on washing care, the washing-care of clothing belongs to a complex process including water flow, detergent, mechanical agitation, which easily occurred the decline of clothing performance when clothing being improper washing.…”
Section: Introductionmentioning
confidence: 99%
“…The seams were sewn by core spun threads and cut polyester threads and found that fabric structure, fabric thickness and stitch density in uenced the seam strength and e ciency signi cantly. (Hui et al, 2017) investigated the in uence of the modulus of elasticity, elongation at break, tensile strength, breaking strength of seam of four identical types of waterproof fabric samples; coating, lm, double-layer composite and denim fabrics. They produced lapped and superimposed seam by using core spun thread (lockstitch 301) at 4 SPCm and found that the denim had the highest seam strength and coating increased the strength but reduced exural rigidity signi cantly.…”
Section: Introductionmentioning
confidence: 99%